Proteomic Analysis Provides Insights on Venom Processing in Conus textile - Tayo, Lemmuel L. (2010)
Conus species of marine snails deliver a potent collection of toxins from the venom duct via a long proboscis attached to a harpoon tooth. Conotoxins are known to possess powerful neurological effects and some have been developed for therapeutic uses. Using mass-spectrometry based proteomics, qualitative and quantitative differences in conotoxin components were found in the proximal, central and distal sections of the C. textile venom duct suggesting specialization of duct sections for biosynthesis of particular conotoxins. Reversed phase HPLC followed by Orbitrap mass spectrometry and data analysis using SEQUEST and ProLuCID identified 31 conotoxin sequences and 25 post-translational modification (PTM) variants with King-Kong 2 peptide being the most abundant. Several previously unreported variants of known conopeptides and were found and this is the first time that HyVal is reported for a disulfide rich Conus peptide. Differential expression along the venom duct, production of PTM variants, alternative proteolytic cleavage sites, and venom processing enroute to the proboscis all appear to contribute to enriching the combinatorial pool of conopeptides and producing the appropriate formulation for a particular hunting situation. The complimentary tools of mass spectrometry-based proteomics and molecular biology can greatly accelerate the discovery of Conus peptides and provide insights on envenomation and other biological strategies of cone snails.